2020
DOI: 10.1038/s41598-020-61971-7
|View full text |Cite
|
Sign up to set email alerts
|

Double-Stranded DNA and NETs Components in Relation to Clinical Outcome After ST-Elevation Myocardial Infarction

Abstract: Neutrophil extracellular traps (NETs) have been implicated in atherothrombosis; however, their potential role as markers of risk is unclear. We investigated whether circulating NETs-related components associated with clinical outcome and hypercoagulability in St-elevation myocardial infarction (STEMI). In this observational cohort study, STEMI patients admitted for PCI (n = 956) were followed for median 4.6 years, recording 190 events (reinfarction, unscheduled revascularization, stroke, heart failure hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 41 publications
1
44
0
Order By: Relevance
“…Liu et al 16 demonstrated that neither cell-free DNA nor MPO-DNA complexes sampled from the periphery were predictive of in-hospital MACE post-STEMI. Similarly, Langseth et al 17 observed that circulating NET biomarkers (dsDNA, MPO-DNA, H3(cit)) were not predictive of MACE. However, increased circulating levels of dsDNA, but not MPO-DNA or H3 (cit), were associated with increased risk of long-term allcause death.…”
Section: Neutrophil Count Xmentioning
confidence: 91%
See 3 more Smart Citations
“…Liu et al 16 demonstrated that neither cell-free DNA nor MPO-DNA complexes sampled from the periphery were predictive of in-hospital MACE post-STEMI. Similarly, Langseth et al 17 observed that circulating NET biomarkers (dsDNA, MPO-DNA, H3(cit)) were not predictive of MACE. However, increased circulating levels of dsDNA, but not MPO-DNA or H3 (cit), were associated with increased risk of long-term allcause death.…”
Section: Neutrophil Count Xmentioning
confidence: 91%
“…However, increased circulating levels of dsDNA, but not MPO-DNA or H3 (cit), were associated with increased risk of long-term allcause death. 17,18 While other studies have shown the utility of peripheral NET burden for predicting MACE in patients with CAD, 13,14 this does not seem to translate into a utility for predicting MACE following AMI. 16,17 However, this statement comes with a caveat: the study of NET biomarkers for MACE is in its infancy.…”
Section: Neutrophil Count Xmentioning
confidence: 99%
See 2 more Smart Citations
“…The release of intracellular contents, which is called neutrophil extracellular traps, is critical for killing bacteria in infection and sepsis [3]. Current studies have shown that NETs and their elements can cause organ injury, coagulation disorders, autoimmune diseases, and thromboembolism [20]. Although NETs are a double-edged sword in sepsis, few studies have focused on their antibacterial function in the early stage of sepsis, during which NETs can trap pathogens and prevent bacterial dissemination [17,18,21].…”
Section: Discussionmentioning
confidence: 99%